Effect of linear polarization illumination mode of partially polarized light on the polarotactic response of locusts - Yang, Bo; Cao, Xinyu; Jiang, Mingyang; Zhang, Pingchuan; Cui, Jinxin; Liu, Qihang (International Journal of Agricultural and Biological Engineering, 2025)
New approaches are required to prevent the plagues of locusts that threaten crop security in many areas of the world. One such approach is to exploit locusts' polarotactic response effect, enabling their aggregation and effective removal from agricultural sites. The current study used linearly partially polarized light with different polarization vectors and a polarotactic response device to test locusts' polarotactic response effect. Results showed that under partially polarized light with linear polarization vectors in the range of 0°-360°, locusts exhibited a sinusoidal-cosine tuning response in specific periods depending on the intensity of the polarization spectrum, and differences in the intensity of the polarization spectrum led to changes in the sensitivity of polarotactic vision at different distances. As the intensity of the illumination increased, the effects of polarized violet, blue, and orange spectra were strongest at far, medium, and close distances, respectively. At the maximum illumination intensity, the differences in the specific sensitivity vector modes at different vision distances were due to variations in the sensitivity of the visual response to the e-vector induced by the optical distance polarization effect of the heterogeneous spectrum. The polarotactic responses were stronger under violet spectrum at 330° and blue spectrum at 0° (360°), while the polarotactic response and aggregation sensitivity were stronger at 240° and the visual trend was sensitive to 180° under orange spectrum. Intriguingly, locusts had different sensitivity thresholds to the intensity of the polarization spectrum, where the polarotactic responses were equal for polarized violet light at a vector of 330° and light energy from various spectral sources. Therefore, combined stimulation with illumination by polarized violet and orange spectra can enhance locusts' polarotactic response effect and regulate the sensitivity of locusts' polarization vision, which provide theoretical support for understanding locusts' polarotactic orientation mechanisms, thereby facilitating the development of polarization-induced light sources for attracting locusts. Key words: Locusta migratoria manilensis; linearly polarized illumination mode; partially polarized light; polarotactic response DOI: 10.25165/j.ijabe.20251806.9399 Citation: Yang B, Cao X Y, Jiang M Y, Zhang P C, Cui J X, Liu Q H. Effect of linear polarization illumination mode of partially polarized light on the polarotactic response of locusts. Int J Agric & Biol Eng, 2025; 18(6): 41–47.